Cosmic ray propagation in turbulent magnetic fields - Lazarian, Alex; Xu, Siyao; Hu, Yue (Frontiers in Astronomy and Space Sciences, 2023)
Propagation of cosmic rays (CRs) in {\xu turbulent and magnetized} astrophysical media is a long-standing problem that requires both understanding of the properties of turbulent magnetic fields and their interaction with energetic particles. This review focuses on {\xu selected recent theoretical findings} made based on the %the advances in the field that have been achieved due to progress in understanding and {\xu simulating} magnetohydrodynamic (MHD) turbulence. In particular, we address the problem of perpendicular and parallel propagation of CRs and identify the conditions when the perpendicular propagation is superdiffusive and diffusive. {\xu For the parallel diffusion, we discuss the problems of the traditionally used diffusion mechanism arising from pitch angle scattering and the possible solutions provided by the recently identified ``mirror diffusion" in the presence of turbulent magnetic mirrors.}